2018
DOI: 10.3122/jabfm.2018.01.170083
|View full text |Cite
|
Sign up to set email alerts
|

Task Delegation and Burnout Trade-offs Among Primary Care Providers and Nurses in Veterans Affairs Patient Aligned Care Teams (VA PACTs)

Abstract: Purpose: Appropriate delegation of clinical tasks from primary care providers (PCPs) to other team members may reduce employee burnout in primary care. However, (1) the extent to which delegation occurs within multidisciplinary teams, (2) factors associated with greater delegation, and (3) whether delegation is associated with burnout are all unknown.Methods: We performed a national cross-sectional survey of Veterans Affairs (VA) PCP-nurse dyads in Department of VA primary care clinics, 4 years into the VA's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 22 publications
3
47
0
Order By: Relevance
“…The percentage of workers with significant levels of stress found in this study is consistent with other studies, which indicate high levels of stress among PHC workers, confirming that workers are affected by problems or damages to their physical and mental health (21,(26)(27)(28)(29)(30) .…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of workers with significant levels of stress found in this study is consistent with other studies, which indicate high levels of stress among PHC workers, confirming that workers are affected by problems or damages to their physical and mental health (21,(26)(27)(28)(29)(30) .…”
Section: Discussionsupporting
confidence: 91%
“…Given the overall rates of burnout and concerns about the need for a larger primary care workforce in the USA, the association between teamwork and a reduced intent to leave the profession is an especially promising finding. Other researchers have found that team-based approaches to care delivery are not associated with increased physician burnout [7,8,9]. The findings in this paper support the idea that primary care practices can improve quality without driving providers away by making sure that team members work together to achieve better, more patient-centered care.…”
supporting
confidence: 74%
“…This is similar to a study conducted in the Veterans Administration system, which found that task delegation from primary care physicians to nurses resulted in more burnout in the nurses. 26 Our study offers some insights into how to make role changes more favorably viewed by MAs.…”
Section: Discussionmentioning
confidence: 99%